FAKTOR-FAKTOR YANG MEMENGARUHI AUDIT REPORT LAG PADA PERUSAHAAN NON KEUANGAN - GLENN MARTINUS MARJONO; ARLENE JANE (E-Jurnal Akuntansi TSM, 2021)
The purpose of this study is to analyze the factors that influence the audit report lag in non-financial companies. These factors are audit quality, board size, audit committee size, audit committee meetings, board gender, company size, profitability, leverage and liquidity. The objects in this study are the non-financial companies listed on the Indonesia Stock Exchange for the year 2016 to 2019 with the sampling method is purposive sampling method. Based on the sampling criteria, the sample of this study amounted to 160 companies with a total of 640 data. This study uses multiple regression analysis. The results of this study showed that the company size and profitability have an influence on the audit report lag. Meanwhile, audit quality, board size, audit committee size, audit committee meetings, board gender, leverage and liquidity have no effect on the audit report lag.